Hubungan antara Diabetes Mellitus dengan Hipertensi pada Pralansia dan Lansia di Puskesmas Rambung Kota Tebing Tinggi - Hormarita Saragih; Meida Nugrahalia; Sartini Sartini (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2019)
The purpose of this study was to determine the relationship between Diabetes Mellitus and Hypertension in Pralansia and the Elderly in Rambung Puskesmas Tebing Tinggi. The research method is carried out descriptively, which is a study conducted with the main objective to make a picture or description of a situation objectively to solve or answer a problem. Based on the results of the study that the relationship between Diabetes Mellitus and Hypertension in Rambung Puskesmas Tebing Tinggi, was quite strong with a value of r = 0.80. The correlation between the disease with 5 factors namely age, sex, blood sugar level, systolic blood pressure and diastolic blood pressure as a whole is very high at r = 0.83. Patients suffering from diabetes mellitus and hypertension are more found in the female sex than men, and people who have a history or hereditary factors of hypertension and diabetes mellitus more than those who have no history, and more patients who first had new diabetes mellitus followed by hypertension